Synthesis of polyurethane-urea microcapsules with perfume for textile application - Rodrigues, S.N. (2011)
This work is a contribution to the introduction of emergent technologies in the textile sector, namely the microencapsulation of fragrances and its application to obtain added-value products. Polyurethane/urea microcapsules with a perfume have been produced using the interfacial polymerization technology for industrial application on textile substrate having in view man suits production. The specific objective of this work is the production of a scented clothing line, which includes: Development of technologies/processes for the production of microcapsules; Incorporation of microcapsules into textile substrates and optimization of the process in a laboratory; Validation and industrial scale-up; Development of testing methods and analysis of the release of the perfume.